Envenenamento por caravela (Physalia physalis) manifestando-se com erupção papulopurpurica - Risk, Yamin José (2012)
We report the case of a 42-year old woman who was envenomed by a Portuguese man-o'-war (Physalia physalis). She presented an anomalous reaction manifested by purpuric papules that appeared after the initial phase of envenoming (around 24 hours later), when linear erythematous and edematous papules were observed. Late-onset reactions in accidents involving cnidarians commonly include chronic eruptions and local pigmentation. © 2012 by Anais Brasileiros de Dermatologia.